Molar shape differentiation during range expansions of the collared lemming (Dicrostonyx torquatus) related to past climate changes. (1st October 2019) - Montuire, Sophie; Royer, Aurélien; Lemanik, Anna; Gilg, Olivier; Sokolova, Natalya; Sokolov, Aleksandr; Desclaux, Emmanuel; Nadachowski, Adam; Navarro, Nicolas
Abstract: The genus Dicrostonyx (the collared lemming) is undoubtedly the small mammal best adapted to the extreme conditions of the arctic environment. The Palearctic collared lemming has been described in numerous European Late Pleistocene localities up to south of France and Croatia. This species experienced climate-driven changes through time, changes mainly observed as repetitive pulses of pan-continental migration, and it thus became a typical indicator of glacial conditions. Using geometric morphometrics on molars, we evaluate the shape changes occurring during the last 100 ky over some dispersal events in Western Europe. The results point out that Dicrostonyx torquatus has a large intra-population variation with a homogenous morphology, regardless of the origin of the individuals. A temporal trend leading to a more complex tooth with a differentiated anterior loop on the first lower molar was observed. An additional effect of the distance from the core populations was also described with a more peculiar shape for the most western populations of France. These temporal and geographical trends might relate to the different migratory pulses documented from ancient DNA haplotypes.